Gastrointestinal nematodes of sheep and cattle : biology and control - Sutherland, Ian , 1962-; Scott, Ian , 1967- (Wiley-Blackwell, 2010)
A unique resource for all those interested in the impact of worms on livestock, the anthelmintics used to get rid of them and the emerging problem of anthelmintic resistance. This book provides an over-arching view of past, present and suggested future strategies for control of gastrointestinal nematode parasites in sheep and cattle.